Adaptive Discrete Filters for Telephone Channels Based on the Wavelet Packet Transform - Ameen, Siddeeq Y.; Al-Shalchi, Abbas A.; Kasim, Vian S. (Nahrain University College of Engineering Journal, 2009)
The wavelet transform provides good and in many times excellent results when used as a basic block transform in many systems such as electronic, communication, medical and even chemical systems. The paper uses the wavelet packet transform to adjust the tap gains of the adaptive filter used in channelequalization and estimation. The results using the wavelet technique achieve good improvements in convergence time over the ordinary LMS algorithm. The two systems were compared on full mathematical and simulation basis. Learning curves for adaptive channel equalization and adaptive channel estimation using wavelet packet transform with different mother functions, different level decompositions, different step sizes, different levels of signal to noise ratio,different telephone channels and different filter sizes were compared with conventional LMS adaptive channel equalization and channel estimation. The simulation results carried out using the MATLAB package version 6.1, demonstrate the efficiency of the proposed technique.